The role of artificial intelligence as a teacher’s ally: El papel de la inteligencia artificial como aliada del docente - Gonzales Ticona, Yoshida; Duran Peñaranda, Eddy (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
Lesson planning, content creation, grading, and tutoring are some of the activities that teachers deal with everyday. This can leave little time to prepare a class with varied activities; representing a heavy workload for teachers, especially if teachers have a large group of students. In this context, Artificial intelligence can help teachers with different activities without increasing work hours in teaching and learning. A literature review of Scopus, DOAJ, Scielo, Latindex, Google Scholar was performed to gain a comprehensive understanding of existing research and scholarly debates related to ways artificial intelligence can help educators. Not only can AI help teachers with different activities in the planning and content of a class, but it can also help improve the teaching approach and keep students focused. In this context, a sample of 214 students was surveyed to gather information about their experiences with different aspects of the teaching approach used in the classroom and how AI can help. Also, an interview with students was conducted to gather more profound information about their perception of the use of AI in the classroom. The findings revealed that the use of a traditional approach, dissertation of teachers with little intervention of students, makes it hard to keep focused in class. However, other approaches may require more investment of time; this is where AI becomes an ally of a teacher allowing them to spend less time on teacher daily activities and concentrate more on individualized learning and deepening a topic. In this way, the classroom is transformed into an environment where students can increase the development of their skills and expand their knowledge.